The Impact of the Supply Chain Strategy on Accounting Social Responsibility to Assess Financial Performance in Iraq - Abid Aljanabi, Abid Kalaf; Ahmed Nouri, Muqdad (International Journal of Supply Chain Management, 2019)
Social responsibility has achieved tremendous attention by academicians and practitioners to focus on social responsibility accounting. However, many studies around the globe have been conduct to measure the outcomes of social responsibility accounting. This paper presents the impact of applying the supply chain strategy (SCS) on the agribusiness field to optimize productivity and decreasing cost which will have a direct impact on the net income of the organization. The inconclusive results of earlier studies stimulated this research to social responsibility accounting-financial performance. The equivocal results of this phenomenon urge this study to investigate the role of other factors in the relationship of social responsibility accounting and financial performance. For the reason, this study examines the mediating role of firm’s advertisement for CSR activities to spread awareness among society and stakeholders. The results of this study revealed that CSR advertisement plays a very important role to build positive perception about social activities among stakeholders and society. The mediation test of Barron and Kenny illustrated that the relationship between social responsibility accounting and financial performance became insignificant when mediating variable CSR advertisement measured by advertisement cost was statistically controlled. This proves that CSR advertisement is necessary for firm to convey message to its stakeholders and society about social activities initiatives. The Firms can only receive true benefits of social responsibility accounting when stakeholders and society are fully aware of CSR initiatives of firms. The findings of this study provide the new insights for literature on social responsibility accounting. Moreover, the firms should focus on preparing social performance reports to inculcate in annual reports. Similarly managers can draw guideline while making business strategy to incorporate social responsibility accounting to obtain fruitful benefits.